Sensory Profiles and Lactic Acid Bacteria Density of Tape Ketan and Tape Singkong in Bogor - Uswatun Hasanah; Haqqifizta Ratihwulan; Lilis Nuraida (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Tape ketan (fermented glutinous rice) and tape singkong (fermented cassava) are traditional Indonesian foods produced by fermenting carbohydrate sources using ragi as starter culture. Those products known to contain high number of lactic acid bacteria (LAB). The purpose of the study was to evaluate the sensory characteristics of tape ketan and tape singkong from different household industry in Bogor, to identify the sensory profile, and to evaluate the correlation between LAB density and sensory attribute. The research was started by survey to household tape industries, followed by sensory analysis of rating hedonic and Quantitative Descriptive Analysis (QDA), and LAB analysis. Data analysis of rating hedonic was done by ANOVA and post-hoc Duncan test, while data analysis of QDA was done by Principle Component Analysis (PCA). Samples of tape ketan were taken from two different home industries (BK and LK), while samples of tape singkong were taken from four different home industries (CT, NG, SH, TS). Hedonic rating test showed that the most preferred sample overall was tape ketan BK and tape singkong CT. QDA results showed that tape ketan BK was characterized by its sweetness, rice-like aroma, rice-like taste, and texture, while tape ketan LK was characterized by alcoholic aroma, alcoholic taste, sourness, and color. Tape singkong NG were characterized by sour aroma, alcoholic aroma, alcoholic taste, and color. Specific characteristic of tape singkong CT was bitterness and bitter aftertaste, SH was sweetness, and TS was texture. LAB of tape ketan BK (8,5 log cfu/g) was higher than LK (7,9 log cfu/g). Tape singkong with highest density of LAB was TS (8,1 log cfu/g), followed by CT (7,2 log cfu/g), NG (7,0 log cfu/g), and SH (6,5 log cfu/g). There was no correlation between the density of LAB and descriptive score of sourness, alcoholic taste, and sweetness.